Guadagni in Handel's London: the formation of a voice. (16th August 2021) - Howard, Patricia
Abstract: Guadagni's first visit to London spanned seven years, from the autumn of 1748 to summer 1755. He arrived from the Veneto as an inexperienced singer at the outset of his career, having been expelled from the Cappella di Sant' Antonio in Padua after a mere six months' employment, and, in the subsequent season, taken a couple of 'third man' roles in an undistinguished opera company. In London he quickly developed his career, securing leading roles in Crosa's touring opera buffa company and appearing regularly in concerts both in London and in provincial festivals. But by far the most significant activity was his contribution, from 1750, to Handel's oratorio series. For six Lenten seasons, Handel's music dominated Guadagni's repertory, both in London and in Dublin. Although Handel created only two roles specifically for him, he adapted many others to suit his voice, with Guadagni taking over either those originally written for female voices, including the contralto Susanna Cibber and the mezzo-soprano Giulia Galli, or those which had been performed by his fellow castratos Andreoni and Senesino; in addition, his concert repertory included solos and duets taken from Handel's operas and oratorios. Having arrived in England a raw and untested novice, Guadagni left an accomplished soloist, going on to take 'first man' roles throughout Europe. This article examines the music written for, assigned to and chosen by Guadagni, to trace the part played by Handel's music in forming the singer at the outset of his career, and argues that Handel was, in his turn, well served by Guadagni's distinctive vocal talents.